Optimalisasi Dinas Perindustrian dan Tenaga Kerja dalam upaya pemenuhan hak pelatihan kerja sebagai wujud pengembangan keterampilan kerja di Kabupaten Klaten - Hapsari, Annafi Nur Faisa; Hartanto, Rima Vien Permata; Yuliandari, Erna (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study aims to (1) optimization of industry and labor services in an effort to fulfill the right to job training as a form of job skills development in Klaten Regency, (2) analyzing the inhibiting factors of the Klaten District Office of Industry and Labor in fulfilling the right to job training as a form of developing work skills. This research is a qualitative descriptive study. With data sourcess obtained using observations at the Industry and Labor Office of Klaten Regency and the Sewing Work Training Participants’, food processing and welding Homes, interviews with the Training and Work Placement Section and four sewing job training participant, two new entrepreneurial participants in food processing and welding and documentation that suports the research program. Data collection techniques using observation techniques, interviews and documentation. Data validity was tested using data triangulation amd method triangulation. While the data analysis technique according to Muhadjir with (1) data reduction (2) data presentation (3) conclusions. The results of this research are (1) optimization of industry and labor services in an effort to fulfill the right to job training as a form of job skills development in Klaten Regency, there are several things that are not yet optimal, including a) Not yet having a Job Training Center b) There are still problems with selection process and lack of job training program. Step taken by the Klaten Regency Industry and Labor Service to optimize job training by a) Utilizing Job Training Institutions b) Screening selection participation c) Increasing the number of training according to needs d) Providing other alternatives (2) Inhibiting factors for the industry and labor services in an effort to fulfill the right to job training as a form of job skills development in Klaten Regency, there are two things, including for the poor a) There are some teaching staff who do not have competent certificates and b) The training participant factor. And for people who are not in the poor category, a) There are no Job Training Centers, b) Inadequate infrastructure c) Training participant factors, and d) Programs for job placement are still limited.